Faktor-Faktor yang Mempengaruhi Pendapatan Penjualan Udang di Pasar Parit 1 Kuala Tungkal Kabupaten Tanjung Jabung Barat - Haris, Abd; Rosita, Ratih; Nurdin, Nurdin; Dani, Rian (Universitas Batanghari Jambi, 2024)
This research aims to determine the factors that influence traders' income when selling shrimp at Parit 1 Kuala Tungkal Market. This research uses a qualitative approach. Primary data was obtained from questionnaires distributed to respondents. Secondary data was obtained from data contained in Pasar Parit 1 Kuala Tungkal. Data analysis in this research uses the SWOT analysis method. The results of the research show that the internal and external factors from the resulting SWOT analysis show that shrimp sales show quadrant I, which means that the shrimp business in the Kuala Tungkal 1 trench market is very strong and has the opportunity to get maximum income, in other words the shrimp business can build the trader's economy in the long term . long. The dominant factor that influences traders' income in selling shrimp at Parit 1 Kuala Tungkal Market is a lot of capital to start a business with working hours for trading activities of 13 hours, two in the morning and in the afternoon. Apart from that, the longer it takes to run a business, the longer the business is run, the more regular customers there will be and lastly, the business location is strategic and easy to reach by both pedestrians and two-wheeled vehicles.